2019
DOI: 10.1002/mgg3.794
|View full text |Cite
|
Sign up to set email alerts
|

Fabry pedigree analysis: A successful program for targeted genetic approach

Abstract: Background Fabry disease (FD) is an X‐linked disorder of glycosphingolipid catabolism caused by a deficiency of the lysosomal enzyme alpha‐galactosidase A ( GLA ). FD is still an underdiagnosed disorder worldwide. Moreover, there is delay between symptom onset and Fabry diagnosis of at least 10 years. Family screening offers an important benefit for detection of new patients. The aim of this work is to present the approach along with the results of a targeted genetic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…Genetic testing of at-risk family members may improve the early diagnosis of FD; however, potential barriers have been identified, including screening and treatment costs, local regulations, and cultural issues [ 19 ]. Similar to our targeted genetic approach, several studies have reported the benefits of clinical genetic approaches using genetic counseling and family screening [ 20 , 21 ]. These programs included predictive genetic testing, which could have adverse psychological effects on clients [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic testing of at-risk family members may improve the early diagnosis of FD; however, potential barriers have been identified, including screening and treatment costs, local regulations, and cultural issues [ 19 ]. Similar to our targeted genetic approach, several studies have reported the benefits of clinical genetic approaches using genetic counseling and family screening [ 20 , 21 ]. These programs included predictive genetic testing, which could have adverse psychological effects on clients [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, genetic testing of all at-risk family members (including males and females) should be encouraged [ 44 ]. Ideally, every patient newly diagnosed with Fabry disease should be referred to a medical geneticist for interpretation of the identified genetic variants and a detailed pedigree review [ 34 , 45 ]. However, the pedigree can also be drawn by any healthcare professional who is willing to spend time interviewing index patients and family members, in accordance with international guidelines [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Основной причиной были плохие внутрисемейные связи и отсутствие общения, что часто было связано с географическим фактором. По данным семейного скрининга, проведенного в других странах, количество родственников с БФ, выявляемых на каждого пробанда, было выше и достигало 10 человек [26,27]. При этом у большинства родственников отмечались малосимптомное течение БФ и отсутствие тяжелых органных поражений.…”
Section: результатыunclassified